Akad Wakalah dalam Jual Beli - Rizal, Ahmed (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2022)
Wakalah contract has an important role in buying and selling. This wakalah has the main purpose of providing financing and services in payment traffic and money circulation. The difference between Islamic banks and conventional banks when viewed in terms of its understanding. Wakalah in Islamic law is the delegation of power by one person as the first party to another person as the second party in the matters represented. Wakalah in Arabic means helping, maintaining, delegating, or being a representative acting on behalf of the person he represents. In terms, wakalah means mutual help between individuals in a problem when someone is legally unable or has obstacles to do so. The object being represented can involve property and other personal matters, such as marriage. The legal basis for wakalah is the Qur'an and hadith.